Preliminary Phytochemicals Screening Of Ficus Racemosa Linn. Bark - A.POONGOTHAI; K.P. SREENA; K. SREEJITH; M. UTHIRALINGAM; S. ANNAPOORANI (International Journal of Pharma and Bio Sciences, 2011)
The traditional medicine involves the use of different plant extracts or the bioactive constituents. The study such as ethno medicine keenly represents one of the best avenues in searching new economic plants for medicine. This type of study provides the health application at affordable cost. To find out the phytochemical constituents in the Ficus racemosa bark, the Ficus racemosa bark was collected from the Coimbatore, Tamilnadu, were shadow dried and they were extracted with benzene, chloroform, ethanol, ethyl acetate, methanol and petroleum ether. Phytochemical screening was carried out according to standard procedures. Sugar, protein, alkaloids, flavonoids, sterols and glycoside were found to be present in the extracts.